The Chaos: Improving the Pronunciation of Grade 9 Students - Pantano, Christine Datuin; Ponce, Princess Mae Dela Cruz (JETAL: Journal of English Teaching & Applied Linguistic, 2024)
Pronunciation is taught primarily at the elementary level. It is a skill that students should master throughout their studies so that they can express their opinions clearly. This study aimed to identify Grade 9 students’ mispronounced words and their causes, level of pronunciation, and the exposure of students in pronunciation using the poem titled The Chaos written by Gerard Nolst Trenité. The researchers used a purposive sampling technique by acceptable pronunciation standards to select the respondents who are in level 1 from Grade 9 students in a selected private school in San Jose del Monte, Bulacan. This study utilized Patole’s English Pronunciation Problems to classify the mispronounced words followed by a focus group discussion. The results showed that irregular pronunciation was the most common pronunciation problem encountered by the students. Additionally, two respondents stepped on level 2 and one respondent stepped on level 3 wherein the respondents agreed that companions are a great help for them to pronounce the words because they can correct it right away.